Safety of systemic therapy for noninfectious uveitis. Issue 12 (2nd December 2019) - Ormaechea, Maria Soledad; Hassan, Muhammad; Onghanseng, Neil; Park, Jung Hyun; Mahajan, Sarakshi; Al-Kirwi, Khalid Yusuf; Uludag, Gunay; Halim, Muhammad Sohail; Schlaen, Ariel; Sepah, Yasir J; Do, Diana V; Nguyen, Quan Dong
ABSTRACT: Introduction : The treatment strategies for noninfectious uveitis (NIU) aim to achieve disease remission, prevention of recurrences, and preserving vision, while minimizing the side effects associated with the therapies used. Areas covered : The index review aims to provide a detailed overview of the adverse events and safety parameters associated with the systemic therapies for the management of the NIU. Expert opinion : Despite being the cornerstone of management of acute cases of NIU, long-term corticosteroid use is associated with multi-system side effects, requiring the use of steroid-sparing agents. Adalimumab was recently approved by the FDA for the management of NIU based on the results of VISUAL studies. Similarly, newer drugs targeting various aspects of the inflammatory cascade are being developed. However, until we completely understand the molecular pathways of the inflammatory diseases, the therapeutic profile of these newer agents needs to be broad enough to suppress inflammatory cascade and narrow enough to spare normal cellular processes. Another strategy that has shown some potential in decreasing the systemic side effects is to provide local drug delivery. Therefore, the future of management of NIU is very bright with many novel therapeutic agents and strategies of drug delivery on the horizon.